On allegations of invasive species denialism. Issue 4 (13th March 2019) - Munro, David; Steer, Jamie; Linklater, Wayne
Abstract: Science denialism retards evidenced‐based policy and practice and should be challenged. It has been a particular concern for mitigating global environmental issues, such as anthropogenic climate change. But allegations of science denialism must also be well founded and evidential or they risk eroding public trust in science and scientists. Recently, 77 published works by scholars, scientists, and science writers were identified as containing invasive species denialism (ISD; i.e., rejection of well‐supported facts about invasive species, particularly the global scientific consensus about their negative impacts). We reevaluated 75 of these works but could find no examples of refutation of scientific facts and only 5 articles with text perhaps consistent with one of the 5 characteristics of science denialism. We found, therefore, that allegations of ISD were misplaced. These accusations of science denialism may have arisen because invasion biology defines its subjects—invasive species—based on multiple subjective and normative judgments. Thus, more than other applied sciences its consensus is one of shared values as much as agreed knowledge. Criticisms of invasion biology have largely targeted those subjective and normative judgments and their global imposition, not the knowledge on which the discipline is based. Regrettably, a few invasion biologists have misinterpreted the critique of their values‐based consensus as a denial of their science when it is not. To make invasion biology a more robust and widely accepted science and to avoid unnecessary misunderstandings and conflicts, invasion biologists could be more accepting of perspectives originating from other disciplines and more open to values‐based critique from scholars and scientists outside their field. This recommendation applies to all conservation sciences, especially those addressing global challenges, because these sciences must serve and be relevant to communities with an extraordinary diversity of cultures and values. Abstract : Article impact statement : False, unsupported claims of invasive species denialism threaten diversity, interdisciplinarity, and progress in invasion biology. Abstract : Sobre Argumentos de la Negación de Especies Invasoras Resumen: La negación de la ciencia retrasa las prácticas y políticas basadas en evidencias, por lo que debería ser cuestionada. Esta negación ha sido una preocupación particular para la mitigación de los temas ambientales a nivel mundial, como el cambio climático antropogénico. Las argumentos en contra de la negación de la ciencia deben estar bien fundamentados y basados en evidencias o se corre el riesgo de mermar la confianza del público en la ciencia y en los científicos. Recientemente, se identificó que 77 trabajos publicados por académicos, científicos y escritores de ciencia contenían negaciones sobre las especies invasoras (ISD, en inglés) (es decir, el rechazo de datos bien respaldados sobre las especies invasoras, particularmente el consenso científico mundial sobre sus impactos negativos). Reevaluamos 75 de estos trabajos pero no pudimos encontrar ejemplos de refutación de datos científicos y sólo cinco de los artículos tuvieron texto quizás consistente con una de las cinco características de la negación de la ciencia. Por esto encontramos que las acusaciones de ISD eran inapropiadas. Estas imputaciones de negación de la ciencia podrían haber surgido a razón de que la biología de la invasión define a sus sujetos – las especies invasoras – con base en múltiples juicios subjetivos y normativos. Así, más que en otras ciencias aplicadas, el consenso de la biología de la invasión consiste tanto de valores compartidos como de conocimiento compartido. Las críticas hacia la biología de la invasión se han enfocado principalmente en esos juicios normativos y subjetivos y en su imposición global, no hacia el conocimiento sobre el que se basa la disciplina. Lamentablemente, unos cuantos biólogos de la invasión han malinterpretado las críticas a su consenso basado en valores como la negación de su ciencia, cuando no lo es. Para hacer de la biología de la invasión una ciencia más fuerte y con mayor aceptación y para evitar malentendidos innecesarios y conflictos, los biólogos de la invasión podrían estar más dispuestos a aceptar las perspectivas que se originan en otras disciplinas y más abiertos a las críticas basadas en valores dadas por los académicos y los científicos que están fuera de su campo de investigación. Esta recomendación aplica para todas las ciencias de la conservación, especialmente para aquellas que tratan las dificultades globales, ya que estas ciencias deben servir y ser relevantes para las comunidades con una diversidad extraordinaria de culturas y valores. 摘要: 否定科学主义阻碍了基于证据的政策和实践, 应受到挑战。它特别关注的一个内容是应对全球环境问题, 如人类导致的气候变化。然而, 对否定科学主义的指控也必须有理有据, 否则会损害公众对科学及科学家的信任。最近, 77 篇由学者、科学家和科学作家发表的文章被认为包含入侵物种否定主义的思想（即拒绝接受关于入侵物种的确凿事实, 特别是其负面影响的全球科学共识）。我们对其中 75 篇文章进行了重新评估, 但没有发现其中存在反对科学事实的例子, 只有 5 篇文章可能符合否定科学主义五项特征中的一项。因此, 我们认为对入侵物种否定主义的指控存在不妥之处。出现这些对否定主义的谴责, 可能是因为入侵生物学对其研究对象——入侵物种的定义基于许多主观、规范性的判断。因而相比于其它应用科学, 入侵生物学中的共识既有共同价值观, 也有共享知识。对入侵生物学的批评主要针对那些主观和规范性的判断及其在全球范围内的实施, 而不是该学科基础的科学知识。令人遗憾的是, 一些入侵生物学家错误地将对其基于价值观的共识的批评看作是对科学研究的否定, 而事实并非如此。为了使入侵生物学这门学科更加健全、得到广泛接受, 同时避免不必要的误解和冲突, 入侵生物学家应更多地接受来自其它学科的观点, 并以开放的心态听取其它领域的学者和科学家基于价值观的评价。这一建议适用于所有的保护科学领域, 特别是那些应对全球挑战的领域, 因为这些科学必须服务并紧密联系文化和价值观高度多样化的群体。【翻译: 胡怡思; 审校: 聂永刚】